39 Improving Orthopaedic Morbidity and Mortality Meetings at a District General Hospital. (19th August 2022) - Hunt, C; Duke, K; Conyers, R; Plail, J; Hibbard, A; David, L
Abstract: Aim: M&M meetings are an integral part of Clinical Governance but can be of varying quality. They should be a learning platform and represent an opportunity to work across disciplines. We identified that these standards were not being met in our department and have sought to improve this. Method: We compared three Orthopaedic M&M meetings against standards set out by both the Royal College of Surgeons and Physicians. Initial results suggested that documentation during the meetings did not meet these standards. A template was created with guidance from the Royal Colleges which aimed to encourage reflection and consideration of agreed actions. This was embedded and is now part of the M&M meetings. A brief educational intervention was also undertaken during the first M&M meeting post-intervention. Results: Data was obtained regarding the new presentation template and format. Compliance with RCS guidelines went from an aggregate 53% to 80%, following intervention. Qualitative data sought via a survey revealed agreement that the new template is superior to the old model in including relevant information, facilitating constructive discussion, and identifying learning points. Conclusions: The new template has been well received and has helped facilitate more useful discussions around how to improve patient care. Comparison of the presentations against RCS guidelines has shown an improvement in the quality of data collected and presented. We will continue to re-audit areas such as identifying learning points to better refine and define the outcomes of M&M meetings for the benefit of patients and the multi-disciplinary team.